Overall survival according to time-of-day of combined immuno-chemotherapy for advanced gastric cancer: a propensity score-matched analysis - Cheng, Chong; Cheng, Xiaqin; Wang, Tiejun (Frontiers in Immunology, 2025)
PurposeThe impact of time-of-day administration (ToDA) of immune checkpoint inhibitor (ICI) on patient outcomes across multiple cancer types is increasingly being elucidated. Following the results of the CheckMate-649 study, chemotherapy combined with immunotherapy has been established as the standard first-line treatment for advanced gastric cancer (GC). A thorough investigation of the relationship between ICI infusion timing and patient outcomes within this combined regimen holds considerable potential to enhance and optimize clinical treatment strategies.MethodsWe conducted a retrospective analysis of patients with advanced GC from West China Hospital, Sichuan University, who received first-line chemotherapy combined with ICIs between January 2020 and September 2024. Patients who received fewer than two doses of ICIs were excluded. Follow-up continued until May 2025. The primary endpoint was overall survival (OS), defined as the time from initial ICI infusion to death from any cause. Secondary endpoints included progression-free survival (PFS), objective response rate (ORR), and adverse events (AEs). Propensity score matching (1:2 ratio, caliper width 0.1) mitigated confounding factors. The impact of ICI infusion timing (after 1630h) on OS and PFS was evaluated using Cox proportional hazards regression. ORR and AEs were assessed with either the Chi-square test or Fisher’s exact test. To further assess the robustness of our findings, sensitivity analyses were conducted using infusion proportion thresholds of 30%, 40%, and 50% at the fixed time point of 1630h, along with time-point sensitivity analyses at 30-minute intervals across the 1500h to 1700h period.ResultsAmong 214 patients, 50 patients received ≥20% of ICI after 1630h (Group A), while 164 patients received <20% (Group B). Before propensity score matching, patients in Group B exhibited significantly shorter OS compared to those in Group A (median 15.4 vs. 21.4 months, HR = 1.64, P = 0.014). After matching, the Group B (44 patients) continued to demonstrate significantly shorter OS than Group A (86 patients) (median 15.4 vs. 22.4 months, HR = 1.82, P = 0.013). Multivariable analysis confirmed these findings. No significant differences were found in PFS, ORR, or AEs (all P>0.050). Sensitivity analysis further validated the robustness of the results.ConclusionEarly ToDA of ICIs is associated with longer OS in patients with advanced GC receiving first-line chemotherapy combined with ICIs. Randomized clinical trials are required to validate these findings.